2019
DOI: 10.3390/ijms20040883
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analyses Provide Novel Insights into Heat Stress Responses in Chieh-Qua (Benincasa hispida Cogn. var. Chieh-Qua How)

Abstract: Temperature rising caused by global warming has imposed significant negative effects on crop qualities and yields. To get the well-known molecular mechanism upon the higher temperature, we carefully analyzed the RNA sequencing-based transcriptomic responses of two contrasting chieh-qua genotypes: A39 (heat-tolerant) and H5 (heat-sensitive). In this study, twelve cDNA libraries generated from A39 and H5 were performed with a transcriptome assay under normal and heat stress conditions, respectively. A total of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…After cucumber fruit skin was air-dried, the epidermis cells were visualized under a HITACHI SU8020 variable pressure SEM (Hitachi, Japan). For TEM assay, fruit skin were cut into small pieces, and were collected for fixation, and the process was performed as according to Wang et al (2019) [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After cucumber fruit skin was air-dried, the epidermis cells were visualized under a HITACHI SU8020 variable pressure SEM (Hitachi, Japan). For TEM assay, fruit skin were cut into small pieces, and were collected for fixation, and the process was performed as according to Wang et al (2019) [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…The qRT-PCR reaction was performed on ABI PRISM 7900HT machine (Applied Biosystems, USA) by using the SYBR Premix Ex Taq Kit (TaKaRa, Japan), and qRT-PCR reaction process was performed according to Wang et al (2019) [ 54 ]. All primers used in qRT-PCR were listed in Table S 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Morimoto et al [66] found that BPM-CUL3 E3 ligase could modulate the heat stress response and prevent an adverse effect of excess DREB2A on plant growth in Arabidopsis. The expression of six ubiquitin-protein ligase genes were detected to be significantly increased in the heat-tolerant chieh-qua cultivar 'A39' when compared with the heat-sensitive cultivar 'H5' after four days of heat stress [50]. In the present study, we identified nineteen ubiquitin-protein ligase genes, among which, the expressions of fifteen genes (LOC107428626, LOC107424969, LOC107413314, LOC107413313, LOC107422277, LOC107426882, LOC107420280, LOC107415107, LOC107432321, LOC107419944, LOC107404052, LOC107431904, LOC107411111, LOC107431883, LOC107403709)were all higher in 'HR' than in 'HS' at 3, 5d (Fig 7, S3 Table), indicating that the high expression of these ubiquitin-protein ligases after prolonged heat stress may help 'HR' confer stronger adaptability to high temperature than 'HS'.…”
Section: Plos Onementioning
confidence: 99%
“…For ultra-structural observation, the sixth leaf from the top was removed from 4 random plants in each treatment time point (n = 3) for each cultivar and then the leaf tissue adjacent to the vein were cut into 1 mm Ă— 2 mm and fixed immediately by immersion in 4% glutaraldehyde overnight, then washed with 0.1 M PBS (pH7.4) for 15 min three times. After post fixation in 1% osmium tetroxide for 5 h at 20ËšC, the fragments were washed with 0.1 M PBS for 15 min three times and gradually dehydrated in ethanol (30,50,70,80,90,95 and 100% ethanol for 1 h), then immersed in 3 ethanol: 1acetone (v/v), 1 ethanol: 1acetone (v/v), 1 ethanol: 3 acetone (v/v) for 30 min, respectively. The fixed samples were embedded in SPIpon812 epoxy matrix (SPI, Chem) and observed by transmission electron microscopy (HT7700, Hitachi, Tokyo, Japan).…”
Section: Physiological Measurements and Ultra-structural Observationmentioning
confidence: 99%
“…var. Chieh-Qua How) displayed differentially expressed genes (DEGs) related to Hsps, ubiquitin-protein ligase, transcription factors (TFs), and pentatricopeptide repeat-containing proteins were significantly changed after heat stress [ 22 ]. A comprehensive analysis of the Korean fir ( Abies koreana ) genes expressed under heat stress using transcriptome analysis revealed 204 transcription factors and 189 Hsps as differentially expressed [ 23 ].…”
Section: Introductionmentioning
confidence: 99%